Impact of the World Trade Organization on acceding countries: A Descriptive Study - Kholoud Ali Abdullah Alzahrani (International Journal of Law Research and Studies, 2025)
The World Trade Organization includes the majority of the countries of the world, as the World Trade Organization is considered a global international organization as it aims to raise the living standards of the countries that join it and continue to grow real income and increase production, and aims to trade in services and goods through the optimal use of the resources of the countries of the world in accordance with the development goals they seek, while taking care to protect, preserve and support the environment in a manner appropriate to the needs and concerns of each of them, and the accession of countries to it has many effects on those countries, including positive effects that increase the economy and resources of the state and speed its trade procedures, including some negative effects. This study was divided into one article with four demands in which we dealt with the effects of joining the World Trade Organization, whether developed, developing or other countries, and whether these effects are negative or positive, in addition to clarifying the impact of the Kingdom of Saudi Arabia's accession to the World Trade Organization (WTO). The study reached several results, the most important of which are: The World Trade Organization has a clear economic impact on developed countries, increasing their access to global markets as well as benefiting from the resources of developing countries, which led to an increase in the productivity of developing countries and the recovery of their trade, and the Kingdom of Saudi Arabia established a special body to organize its foreign trade transactions under the name of the General Authority for Foreign Trade. The study concluded with several recommendations, the most important of which are: Reducing production costs for developing countries and reducing taxation fees.
Keywords: World Trade Organization; Trade; Developed Countries; Developing Countries